Sistem Informasi Layanan Perkara Pada Pengadilan Agama Kelas IA Jambi - Azi Akbar, Ahmad; Fachruddin, Fachruddin (LPPM Universitas Dinamika Bangsa, 2024)
The Class IA Jambi Religious Court is one of the judicial bodies in charge of deciding, adjudicating and resolving cases at the first level between people of the Islamic faith in the fields of marriage, inheritance, wills and grants whose case data is still conventional. The purpose of this research is to analyze the running system for problem services at the Class IA Jambi Religious Court and to design a prototype web-based problem service. So that there are problems, namely the process of requesting court submissions to the case settlement process requires time and money, information about case services such as trial agendas, trial results, and others can only be obtained by going to the office directly, and the process of archiving trial data or preparing reports takes time quite a long time. Solutions to problems that occur by analyzing and designing a web-based problem service information system using the storyboard prototype development method and the unified model language system model using use case diagrams, activity diagrams, and class diagrams. The results of system development can display plaintiff data, service data, service data requests, trial schedule data, trial results data and produce reports that can be printed according to their needs.